Effect of heavy metals on soil and crop pollution in Ukraine – a review - Oksana Sytar; Natalija Taran (Journal of Central European Agriculture, 2022)
The presented review discusses current situation with heavy metal pollution in the various regions of Ukraine and possible pollution of important crop. It is suggested that violent conflict of 2022 in Ukraine may cause development of polluted areas with Pb, Ni, Cr, Cu. Especially such tendency is dangerous for Ukrainian regions with high level of heavy metals level where is military conflict was in an active phase: Donetsk, Zaporizhia, Kyiv, Lugansk, Sumy, Kharkiv, Kherson, Chernihiv, Mykolaiv, Zhytomyr, Dnipropetrovsk, and Odessa regions. The analysis of monitoring data related heavy metals pollution has been described in regions of Ukraine. Current ccharacteristics of major crop production areas in Ukraine regarding their possible yield production and presence of heavy metals in the soil are presented. Near 70% of planted areas for major exported plants in the areas of conflict may be under additional increased effects of heavy metals. The wheat, corn, barley, rapeseed, sunflower have been presented and discussed their cultivation potential as major crops in Ukraine. It is recommended to use modern technologies of phytoremediation with use crop rotation of plants hyperaccumulators of heavy metals at these areas afterword's.